2015
DOI: 10.2147/rip.s52980
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii infection and neuropsychiatric disease: current insight

Abstract: Toxoplasma gondii has always been associated with severe medical disease when acquired congenitally or under immunocompromised conditions. However, in the last decade, intensive research has shed light on Toxoplasma gondii as a latent chronic infection producing distinct neuropsychiatric symptoms and alterations in its intermediate hosts, such as humans and rodents. The peculiarities described range from the well-established attenuated odor aversion paradigm toward cat urine, in infected rodents to significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…It has been recently suggested that chronic infection with T. gondii in the brain correlates with changes in neuronal architecture, neurochemistry, and behaviour [7]. Several studies documented the connection between infection with T. gondii and certain mental health disorders such as schizophrenia [8], bipolar disease [9], suicide attempts [10], personality disorders [11] and episodes of self-directed violence [12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been recently suggested that chronic infection with T. gondii in the brain correlates with changes in neuronal architecture, neurochemistry, and behaviour [7]. Several studies documented the connection between infection with T. gondii and certain mental health disorders such as schizophrenia [8], bipolar disease [9], suicide attempts [10], personality disorders [11] and episodes of self-directed violence [12].…”
Section: Introductionmentioning
confidence: 99%
“…For example, gastrointestinal inflammation has been associated with schizophrenia (Severance et al, 2012(Severance et al, , 2016. The gut mucosal immune system has a crucial role in the systemic dissemination of T. gondii (Hinze-Selch, 2015). In the KEGG enrichment, two gut mucosal immune-related pathways [inflammatory bowel disease (ssc05321) and intestinal immune network for IgA production (ssc04672)] were shared among the infected brains at 10, 25, and 50 DPI.…”
Section: Inflammatory Responsementioning
confidence: 99%
“…Transmission from domestic animals to humans and wildlife Although the mechanisms are unknown a growing body of data indicates that they are complex, comprising humoral, immune, neurotransmitter, epigenetic, genetic, and structural effects 19 .…”
Section: Halicephalobus Gingivalismentioning
confidence: 99%